Anatomy, biomechanics, and clinical advances of proximal tibiofibular joint in pain management - Zhai, Tianjun; Jiang, Fengyan; Feng, Wei; Chen, Zhaohui (Frontiers in Surgery, 2025)
This article presents a descriptive review focused on the proximal tibiofibular joint (PTFJ), a synovial plane joint located posterolaterally beneath the lateral tibial plateau. The PTFJ facilitates axial load transmission, allows subtle tibiofibular motion, and works in conjunction with the distal syndesmosis to preserve ankle and knee function. Dysfunction—resulting from anatomical variation, trauma, instability, or degeneration—can lead to pain, mobility impairment, and nerve compression. Clinical conditions such as osteoarthritis and peroneal nerve entrapment are increasingly linked to PTFJ pathology. Novel therapies like proximal fibular osteotomy (PFO) have shown promise in treating medial compartment knee osteoarthritis based on the uneven settling theory. Diagnosis involves multimodal imaging, and management spans conservative, interventional, and surgical approaches. A comprehensive understanding of the PTFJ supports accurate diagnosis and the development of effective treatment strategies.